Effect of Different Magnetic Fields on The Relative Efficiency and The Energy Resolution of Nai(TI) Detectors - AL-Dahan, N.M.SR. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of different magnetic Jiel ds on the Nal(Tl) scintillation detector of (3"x3") and (1.5"x1.5")   sizes was studies, using the radioactive source Cs-137.Two type:; of coils (A,B)  were used to produce the magnetic fields. The coil "A" is cylindrical of "9cm" diameter and "9cm" length , and of2500 turns.The measurements were taken in two positions ;the first when the crystal inside the coil ,and the second, the PMT inside the coil . The range of the magnetic field was (0.35,0.61,0.84,1.1 1,1.37,1.62,1.87 and2.12) mT.The coil "D" consists of two circular and parallel coils of "12 em" distance between them and of "18.5 em" diameter of each other and of "125" turns. rive  locations ,due to the distance between the center of coil "B" and the center of the crystal face , the measurements were taken in magnetic field range (0.33,0.61 ,0.89,1 .22,1.54,1.8,2.1 and 2.4)mT.The experimental results show : the photo peak and total rel ative efficiency de:reases with increasing the magnetic intensity ,and the energy resolution would be worse with i L